INVESTIGATING THE EXPRESSION OF NOVEL GENES IN HEART CELL (The Research of Medical Science Review, 2025)
To determine the expression of myocardin in dilated cardiomyopathy, the cross-sectional study was done on dilated cardiomyopathic subjects visiting Fatima Memorial Hospital Lahore during Jan, 2016 – June, 2016. The subjects were divided into two groups as diseased group (n=20) & control group (healthy persons) (n=20). A self-designed questionnaire was filled by each subject to collect data regarding age, exercise and disease history. RNA was isolated from the blood samples of studied subjects. After quantification of RNA by nano drop, cDNA was prepared and RT-PCR was performed for expression of myocardin. Statistical analysis was done by using SPSS. The expression level of Myocardin in DCM i.e. diseased group (n =20) was in the range of 1.6 to 7.5 with a mean value of 3.66± 0.357. While for control group containing healthy persons (n=20), gene expression level was 1.00 as assessed in blood samples of control group. The expression of myocardin gene has been increased in dilated cardiomyopathic subjects.